Website Security Analysis Using Penetration Testing Method - Tio Rahmadi; Khairil Khairil; Reno Supardi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Penetration testing is one method to secure websites from attacks by irresponsible people or hackers. With this method, website owners can find out where the vulnerabilities are on the website. This study aims to test the level of security on a website. The penetration testing method used is the Zero Entry hacking method with 4 stages, namely: reconnaissance, scanning, exploitation, and post exploitation and maintaining access. The results obtained from this study are that High Court of Bengkulu’s website has 4 vulnerabilities that have been successfully exploited, there is 1 vulnerability that is in the High category, and 3 vulnerabilities that are categorized as medium, the results of the exploitation test that were successfully carried out were measured using the Common Vulnerability Scoring System (CVSS), therefore it can be seen that the overall level of vulnerability of High Court of Bengkulu’s website has a score of 6.0 (medium), which means that High Court of Bengkulu’s website is quite safe against cyber attacks.